Problems of remote detection of chemical explosives and fissile materials using neutron-activation diagnostics method - Dubina, V.N.; Chornyj, A.V.; Chornyj, V.V. (Вопросы атомной науки и техники, 2014)
This paper presents results of computer simulation of nuclear processes (using Geant4 9.0 package) for neutrons passing through a shell-free explosive model and through a model of military load containing some fissile material. Spectral distributions of γ-quanta were calculated for the neutron with fixed energy at different points of time after irradiation. The programs were designed using C++ and function under execution control of OS Red Hat LINUX 6.2 FEDORA.